Comparison of infection of Citrus tristeza closterovirus in Kinnow mandarin (Citrus reticulata) and Mosambi sweet orange (Citrus sinensis) in Pakistan. (December 2015) - Abbas, Mazhar; Khan, M.M.; Mughal, S.M.; Ji, P.
Abstract: The study was conducted in commercial orchards in three major citrus producing regions of Pakistan to compare the infection of Citrus tristeza closterovirus (CTV) in leading citrus cultivars. In total, 450 trees of mandarin ( Citrus reticulata cv. Kinnow) and sweet orange ( Citrus sinensis cv. Mosambi) were tested for the presence of CTV using double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA). The serological analysis showed that the average infection rate in sweet orange and mandarin was 33.77% and 17.33%, respectively. Serological testing of the collected samples from symptomatic trees also revealed that CTV was widely distributed in the surveyed citrus orchards. Infection rates of CTV in Sargodha, Sahiwal, and Faisalabad districts ranged from 23.33 to 40%, 23.33–36.66%, and 6.66–23.33%, respectively. Absorbance values (OD405nm ) of virus titer in infected sweet orange trees ranged from 0.353 to 1.548 and in mandarin from 0.311 to 0.914. CTV titers in citrus cultivars in Sargodha and Faisalabad districts fluctuated in different seasons. Absorbance values fell below the cut-off point during high summer temperatures and severe winters in both mandarins and sweet oranges. The results indicate that selection of citrus cultivars may play a significant role in developing integrated programs for managing disease caused by Citrus tristeza closterovirus . Highlights: Citrus trees in three major citrus producing regions of Pakistan were assessed for Citrus tristeza closterovirus (CTV). On the basis of serological indexing we observed higher rate of CTV infection in Sweet oranges than Kinnow mandarin. High summer temperatures and severe winters in Pakistan significantly reduce the CTV titer. Assessment of tristeza infection in appropriate months will provide more accurate reading for virus titer.